Tinjauan sistematis tentang faktor-faktor yang mempengaruhi perilaku pemilahan sampah rumah tangga - Apriani, Yunda; Liquiddanu, Eko; Hisjam, Muhammad (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2025)
Rapid population growth has resulted in increased waste production, with projections that global waste will reach 3.4 billion tons by 2050, posing serious environmental challenges. Waste separation and recycling are essential strategies to address this issue, but community participation in waste segregation practices is still lacking. This study aims to identify and analyze the factors influencing household waste separation behavior through a systematic review conducted in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A comprehensive literature search was conducted utilizing the Scopus database, yielding 19 relevant articles and two additional articles identified through a manual search on Google Scholar. The analysis revealed that most studies applied the Theory of Planned Behavior (TPB) to analyze the factors influencing waste separation intentions and actions. Commonly applied variables in research include attitudes, norms, awareness, knowledge, perceived behavioral control, law and regulation, and situational factors. The findings are expected to provide insights for researchers and support creating more effective policies to increase community involvement in sustainable waste management.